Palladium‐Catalyzed Cyclopropanation of Strained Alkenes with 3‐Pinacolatoboryl‐1‐arylallyl Carboxylates. Issue 35 (10th November 2014) - Horino, Yoshikazu; Takahashi, Yu; Kobayashi, Ryota; Abe, Hitoshi
Abstract: The palladium‐catalyzed cyclopropanation of strained alkenes with 3‐pinacolatoboryl‐1‐arylallyl carboxylates was explored. The reactions proceeded smoothly under mild conditions, and the cyclopropanation products were obtained in good to high yields with high diastereoselectivities if CsF, 18‐crown‐6, and molecular sieves were used as additives. The reaction was hypothesized to proceed through the formation of a putative palladacyclobutene intermediate that needed to be considered to explain the observed stereochemistry. Abstract : The palladium‐catalyzed cyclopropanation of strained alkenes with 3‐pinacolatoboryl‐1‐arylallyl carboxylates is described. The reaction proceeds smoothly under mild conditions, and the cyclopropanation products are obtained in good to high yields with high diastereoselectivities if CsF, 18‐crown‐6, and molecular sieves are used as additives.